ABUSE OF SUPERIOR BARGAINING POSITION: DOES THE ASBP INDEED HARM THE COMPETITION? - Doniyor Abduazizov; Nomin-Erdene Purevdash (Journals Park Publishing, 2024)
While some scholars suggest that the concept of Abuse of Superior Bargaining Position (ASBP) bears significant similarities to exploitative forms of abuse of a dominant market position, other scholars argue that there is still controversy and a lack of clarity surrounding the ASBP concept itself. Given this ambiguity in the doctrine, these scholars advocate for a sensible approach that focuses on the actual intended meaning and practical enforcement of ASBP, without unfairly prejudicing or treating any interested parties involved. Through this comparative examination of the legal frameworks and jurisprudential approaches in Japan and Uzbekistan, the article endeavors to shed light on the nuances, similarities, and differences in how ASBP is perceived and operationalized in these two countries. By doing so, the article hopes to contribute to a better understanding of the ASBP doctrine and potentially identify areas where further harmonization or clarification may be needed across jurisdictions.
Keywords: competition law, digitalization, online platforms (marketplaces), market aggregators, market boundary, free goods and services etc.